Integrating Management, Education, and Marketing Strategies in Secondary Schools: A Comparative Qualitative Study in South Jakarta and South Tangerang - Murtini Murtini; Mohamad Irvan Septiar Musti; Ditta Mustika Rakhmawati; Artipah Artipah; Alberto Emmanuel Conti Morales (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study aims to analyze the integration of management, education, and marketing strategies in secondary schools through a qualitative approach. The research was conducted in two schools located in South Jakarta and South Tangerang, involving principals, teachers, management staff, and parents as key informants. The findings reveal how school management strategies are implemented to enhance educational quality while simultaneously building the school’s image through educational marketing practices. The results indicate contextual differences between the two locations, yet both schools face similar challenges regarding competition and the need for innovative marketing approaches. This research contributes to interdisciplinary understanding by highlighting how educational management and marketing strategies can collaborate to strengthen school competitiveness.